Avaliação cognitiva e funcional de idosos usuários do serviço público de saúde e sobrecarga de seus cuidadores - Melo, Beatriz Rodrigues de Souza (2015)
The changes observed in the morbidity and mortality profile, characterized by the greater occurrence of chronic illnesses and possible functional and cognitive losses due to aging, produce specific demands for health care. The objectives of this study was to evaluate and compare the health, functionality, cognition and mood of the elderly and to assess and compare the health and burden of formal and informal caregivers of elderly at three public health institutions with different care profiles (hospitalization, outpatient and long-term). This is an observational, cross-sectional, comparative with a quantitative approach , approved by the Research Ethics Committee . Data were collected in the first half of 2014, with instrument for sociodemographic, health, Mini Mental State Examination (MMSE), the Clock Test, Geriatric Depression Scale (GDS), Basic Activities of Daily Living Scale (Katz ) and Instrumental Activities of Daily Living (Lawton) for seniors, caregivers were applied in the last issue of Zarit Overload Scale and Self Reporting Questionnaire SRQ-20. The sample consisted of 140 elderly persons, with 37 people from a Long-Term Care Institution for the Elderly (LTCIE), 53 users from a teaching hospital and 50 from the Teaching Health Service (USE), and 50 caregivers, 15 formal caregivers anda 35 informal caregivers, located in an interior city in the State of São Paulo, Brazil. Elderly subjects in LTCIE, 54.1 % were male, and most entirely dependent for both BADL (51.4 % ), and to IADL (62.2 % ) and 100 % of the evaluated elderly patients with cognitive decline ( average 6.6 points) . At the Teaching Hospital, 50.1 % male , 58.5 % for independent BADL, IADL and 43.4% to 62.3 % of the elderly patients with cognitive decline (mean 17.3 points). At the USE, 68 % female, 59 % for independent BADL, IADL and 40 % to 48% of elderly patients with cognitive decline (average of 19 points). Regarding the presence of depressive symptoms, the incidence in institutions were 29.7%, 41.5 % and 36 %, respectively. Of formal caregivers, there was a predominance of women (86.7 %), and an average of 7.5 hours daily working hours. Emotional stress was evaluated by SRQ-20, showing data that the question " poor sleep " was the most frequent (53.3 % ), followed by questions "feeling tense, nervous or worried " (40%) and " feel -If tired " (40%), revealing that 26.7% were diagnosed with emotional stress. After application of the latest issue of Zarit Scale, 40 % answered feel" a little overwhelmed" and "moderately overloaded" (26.7%). As for the 35 informal caregivers evaluated, it was revealed that 77.1 % of them lived with the elderly . There was a predominance of women (85.7 %), and 42.9 % represented by children , with care time of 6.5 years and an average of 19,8h a day taking care of the elderly. After burden assessment, 31.4 % reported feeling " a little" overwhelmed and 25.7% "very overwhelmed”, revealing that 17 (48.6%) had mild overload. As for the emotional stress the most reported issues were "feeling tense, nervous or worried" (80%), "sad feeling lately" (62.9 %) and "sleep badly" (60%) revealing that 16 (45.7 %) had emotional stress. The results show that the functional and cognitive impairments were identified in different contexts among the elderly, and the related cognitive decline mainly to old age. About caregivers, higher levels of burden and emotional stress were found in informal caregivers. These results reveal the requirement to look at this population’s needs in the different contexts more closely, planning interventions to improve these people’s health and work conditions.